Menelusuri Rahasia Dibalik Dunia Siber dalam Novel Fake Semu Karya Ele Fountain - Aditya Kurnia Akbar Pratama; Furqan BahrulSahlan; Eva Dwi Kurniawan (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The aim of this research is to determine the use of technology in the cyber world as stated in this literary work. The literary work used the novel genre entitled Fake Semu by Ele Fountain. The problem raised is about the cyber world in the novel. The novel Fake Semu by Ele Fountain is a novel with a theme about the cyber world. This novel explains the plot where technology becomes the only friend in the world. In this novel, Ele tells the story of a world where all needs for food, health, access to digital transactions are fully controlled by technology. Because of this, Ele began to tell about someone who was curious about the digital world and used various forbidden skills in the cyber world to get all the answers to his questions. The method used uses a hermeneutic approach. The findings obtained in the novel are 1) Database, 2) Hacking, 3) Encryption, 4) Spyware, 5) Cypher, and 6) Cyber Minder.